MOTIVASI MAHASISWA NON MUSLIM STUDI DI UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM (STUDI FAKULTAS TARBIYAH DAN KEGURUAN 2015/2016) - Mariati "; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the motivation of the non-muslims students who study at the State Islamic University Sultan Syarif Kasim located at the Faculty of Tarbiyah and Teaching academic year 2015/2016. In this study the authors found four informants / respondents who become the object of study, the four informants were from three departments in the Faculty of Tarbiyah and Teaching. The survey results revealed that all respondents overall say and agree that motivation because of the influence of the parents is the reason for their motivation studies in the Faculty of Tarbiyah and Teaching. While three of the respondents said that the motivation because of the influence from their friends and family is also the reason they are in the study at Faculty of Tarbiyah and Teaching. Only two of four respondents say that they also have the motivation that comes from themself, and students who achieve a CPI score the highest from four informants are students in motivation from themselves so there is no compulsion to study at the Faculty Tarbiyah and Teaching Universitas Islam Negeri Sultan Syarif Kasim. Keywords: Motivation, Non Muslim Students, Faculty of MT and Teaching, UIN SUSKA